Rotational modulation of Saturn's radio emissions after equinox. Issue 12 (3rd December 2016) - Ye, S.‐Y.; Fischer, G.; Kurth, W. S.; Menietti, J. D.; Gurnett, D. A.
Abstract: Saturn kilometric radiation (SKR), narrowband emission, and auroral hiss are periodically modulated due to Saturn's rotation, and the periods were found to vary with time. We analyze Cassini observations of Saturn's radio emissions with the main focus on the four years 2012–2015. It is shown that the rotation rates of SKR north and south were different since mid‐2012 with SKR north being faster until autumn 2013, followed by a 1 year interval of similar north and south rotation rates and phases, before the northern SKR component finally became slower than the southern SKR in late 2014. The dual rotation rates of 5 kHz narrowband emissions reappeared for slightly longer than 1 year after a long break since equinox. Auroral hiss provides an unambiguous way of tracking the rotation signals from each hemisphere because the whistler mode waves cannot cross the equator. Rotation rates of auroral hiss and narrowband emissions are consistent with each other and those of SKR when they are observed at high latitudes in early 2013. The phase difference between SKR and auroral hiss and the intensity of auroral hiss are local time dependent. Key Points: The rotational modulations of Saturn radio emissions are different in each hemisphere and vary over a Saturn year The rotation rate of northern SKR became slower than that of southern SKR in 2015 The phase difference between SKR and auroral hiss and the intensity of auroral hiss are local time dependent